2008
DOI: 10.1182/blood.v112.11.753.753
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Microarray-Based Gene Expression Profiling in the Diagnosis and Sub-Classification of Leukemia: Final Report on 3252 Cases from the International MILE Study Group

Abstract: During the years of 2005 to 2008, the MILE (Microarray Innovations in LEukemia) study research program was performed in 11 laboratories across three continents: 7 from the European Leukemia Network (ELN, WP13), 3 from the US and 1 in Singapore. The first stage was designed as biomarker discovery phase to generate whole-genome gene expression profiles (GEP) from recognized categories of clinically relevant leukemias and myelodysplastic syndromes (MDS). These were C1: mature B-ALL with t(8;14), C2: pro-B-ALL wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This cohort was collected as part of the Microarray Innovations in LEukemia (MILE) study and consisted of 74 favourable risk subjects and 168 NK-AML subjects. 9 , 10 The demographic data for each of these subjects in the MILE Study has previously been published. 9 Using the PGS-ANOVA tool, 7112 probesets were identified that differed significantly in mRNA levels between favourable and NK-AML risk groups.…”
Section: Resultsmentioning
confidence: 99%
“…This cohort was collected as part of the Microarray Innovations in LEukemia (MILE) study and consisted of 74 favourable risk subjects and 168 NK-AML subjects. 9 , 10 The demographic data for each of these subjects in the MILE Study has previously been published. 9 Using the PGS-ANOVA tool, 7112 probesets were identified that differed significantly in mRNA levels between favourable and NK-AML risk groups.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray data from the International Microarray Innovations in Leukemia (MILE) study group was analyzed. Expression of MLL2/KMT2D (probe 231974_at) and MLL3/KMT2C (probe 1557158_at) in 76 CML patients and 73 non-leukemia or healthy bone marrow samples from the MILE study group were obtained through the Bloodspot database [ 13 ] in the form of log2 scaled intensity values [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Main patients' characteristics are summarized in Table 1. All but one patient (P14) included in this study were part of a larger cohort of samples analyzed by GEP during the international 'Microarray Innovation in LEukemia' (MILE) study (11). All patients were randomly selected from a larger cohort of BCP ALL patients.…”
Section: Patient Datamentioning
confidence: 99%